Phyllodes Tumor of the Prostate With Epithelial Intestinal Metaplasia. (June 2018) - Olivas, Andrea D.; Taxy, Jerome; Wolsky, Rebecca; Antic, Tatjana
Abstract : Phyllodes tumor of the prostate is a rare mesenchymal tumor conventionally regarded as a stromal tumor of undetermined malignant potential. While the initial presentation is that of urinary obstruction and/or hematuria, the subsequent clinical behavior is thought to be a function of stromal cellularity and cytologic changes of malignancy. Of histologic interest, the epithelial component of this tumor varies, including intestinal metaplasia, as seen in the present case.